Barriers to Pediatric Sickle Cell Disease Guideline Recommendations - Michael D. Cabana MD, MPH; Julie Kanter MD; Anne M. Marsh MD; Marsha J. Treadwell PhD; Michael Rowland MPH; Peggy Stemmler MD; Naomi S. Bardach MD, MAS (SAGE Publishing, 2019)
National guidelines recommend that providers counsel all patients with sickle cell anemia about hydroxyurea (HU) therapy and screen children with sickle cell anemia annually for the risk of stroke with transcranial Doppler (TCD). We surveyed a national convenience sample of sickle cell disease clinicians to assess factors associated with low adherence. Adherence was 46% for TCD screening. Low adherence was associated with a lack of outcome expectancy (eg, a belief that there would be poor patient follow-up to TCD testing; P < .05). Adherence was 72% for HU counseling. Practice barriers (eg, lack of support staff or time) and a lack of agreement with HU recommendations were associated with low adherence ( P < .05). This study demonstrates that different types of strategies are needed to improve TCD screening (to address follow-up and access to testing) versus HU counseling (to address physician agreement and practice barriers).